Farmers’ Satisfaction with Extension Services in the Organization of Eastern Caribbean States - Wayne G. Ganpat; Nichole Webster; Lendel K. Narine (Journal of International Agricultural and Extension Education, 2014)
The economies of most countries in the Organization of Eastern Caribbean States (OECS) are dependent on farming, most of which is done mainly by small farmers in mixed cropping systems. The government is also the main provider of extension services. This study sought to assess farmers’ satisfaction with the extensions services and identify areas for improvement. Some 462 farmers in five OECS countries were selected and surveyed in 2013. A farmers’ satisfaction index was developed based on 26 statements in a Likert-type scale and used as the dependent variable. Data were analyzed using STATA 9 and descriptive frequencies and multiple linear regression results were presented. Results showed that farmers’ overall satisfaction with extension was moderate. Farmers’ age, gender, education level, size of farm, number of parcels farmed, number of extension visits received, and whether farmers operated on a full time or part time basis significantly influenced farmers’ level of satisfaction. Recommendations included: the redefinition of target farmers, as well as the scope of extension programs for intervention to meet these states ‘food security goals; the improvement of the technical capacities of extension officers; the expansion of group development work; and the increased use of ICTs for information dissemination and the provision of ICT hardware for extension staff
Keywords: Satifcation; Extension; Small Farmers; Caribbean